Pengaruh Fasilitas Teknologi Mesin Self Check In Terhadap Efektivitas Pengguna Jasa Penerbangan Di Bandar Udara Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan - Wardani Winata Putra; Raden Fatchul Hilal (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The world of aviation in this modern era is increasingly developing. This is evidenced by the self-check-in facility provided by the company which greatly facilitates flight service users at Sultan Aji Muhammad Sulaiman Sepinggan Airport Balikpapan where this facility can not only reduce interaction between humans and reduce the intensity of the spread of the Covid 19 virus at that time, this facility can also maximize the effectiveness of passenger time, so that there are no long queues in the use of manual check in. This study aims to determine the Use of Self Check In Technology Affects the Effectiveness of Flight Service Users at Sultan Aji Muhammad Sulaiman Sepinggan Airport Balikpapan and How Much Influence the Use of Self Check In Technology Affects the Effectiveness of Flight Service Users at Sultan Aji Airport Muhammad Sulaiman Sepinggan Balikpapan. This research uses quantitative research methods with data sources in the form of primary data and secondary data. The population in this study is service users who have used the Self Check-In System and the sample in this study is 95 respondents from 2042 existing populations. Data analysis techniques consist of research instruments, namely validity tests and reliability tests and hypothesis tests consisting of simple linear analysis tests, t tests, and determination coefficients. The result of this study is that the use of Self Check In Technology affects the effectiveness of flight service users at Sultan Aji Muhammad Sulaiman Sepinggan Airport Balikpapan has a partial effect in a negative and significant direction. The magnitude of the correlation / relationship value (R) is 0.461. From this output, a coefficient of determination (R Square) of 0.212 was obtained which explained that the effect of the independent variable of self-check-in machine technology facilities on the effectiveness of aviation service users was 21.2.% The remaining 78.8% was influenced by other variables not explained in this study.